TOOL ASSEMBLAGE OF THE MUKHKAI I CAMP, LAYER 7C: DISCUSSING THE CULTURAL CONTENT OF THE END OF THE EARLY PLEISTOCENE OF THE NORTHEASTERN CAUCASUS - Tajmazov, Artur Israpilovic (History, Archeology and Ethnography of the Caucasus, 2023)
The paper examines the tool assemblage from one of the key late Early Pleistocene sites of the North-Eastern Caucasus – the Mukhkai I camp, layer 7c. The tools constitute three differentiated clusters in terms of planigraphy. Despite this division, there are no significant differences in the typological composition of tools among the clusters. Each cluster encompasses both heavy-duty impact tools and small retouched pieces on flakes. Choppers, displaying various modifications of the working edge, particularly those with a narrow cutting edge, predominate in the tool assemblage. Additionally, the assemblage comprises picks (triangular and flat), chisel-like tools, heavy-duty scrapers, knives, notched tools, scrapers, and retouched flakes. The typological composition of the tools at Mukhkai I, layer 7c, generally corresponds to the Oldowan assemblage. Notably, the prominent tool types of the Acheulian technocomplex – handaxes and cleavers – are absent from the lithic industry of layer 7c. However, the production of large flakes and their utilization as blanks for large tools is recorded within this layer. Despite this, such practices did not gain widespread prevalence. Within the excavated area of layer 7c, only three large flakes were unearthed, and each underwent transformation into morphologically complete objects. Examining the collection’s debitage composition suggests that the primary objective of lithic reduction remained the production of small flakes. Mastering large flake production did not precipitate a decisive transformation in the technical and typological characteristics of the industry. From a periodization standpoint, this camp corresponds to the Oldowan industry while exhibiting distinct indicators of the Early Pleistocene large flake industry of the Caucasus, marking the transitional stage between Oldowan and Acheulian. It is plausible that this camp pertains to the initial phase of this transitional period.